دراسة الظروف الجيولوجية والهيدروجيولوجية لموقع سد باشكات في منطقة الحفة باستخدام الطرائق الجيوكهربائية - علي, خليل; ملحم, أشرف (Latakia University Journal -Basic Sciences Series, 2018)
يقع موقع سد باشكات على السفح الغربي لجبل الأنصاري في منطقة الحفة التابعة لمحافظة اللاذقية, حيث تم اختيار هذا الموقع لإنشاء السد. وتهدف هذه الدراسة الجيوكهربائية إلى حل بعض المسائل الجيو-هندسية أهمها: - دراسة طبقة التجوية. - توضيح البنية الجيولوجية لموقع إنشاء سد باشكات. - استكشاف الكهوف والفجوات الكارستية. - تحديد نطاقات الصدوع في الموقع. - تحديد مناطق التشقق واتجاهها العام. - تحديد عامل الامتصاص النوعي المائي للمستويات الجيوكهربائية(q L / min.m). - تحديد المحتوى الطيني للمستويات الجيو كهربائية (β %). - وضع خريطة جيولوجية لمنطقة الدراسة بمقياس (1:2000) وقد استخدمت لحل المسائل المذكورة أعلاه طريقة المقاومية باستخدام تشكيل شلومبرجير للسبر الكهربائي الشاقولي, والسبر الشاقولي الدائري. شمل العمل الحقلي على (34) نقطة سبر موزعة على خمسة بروفيلات. وبنتيجة تفسير نتائج السبر الكهربائي الشاقولي والدائري بالطرائق اليدوية توصلنا إلى وضع خمسة مقاطع جيوكهربائية, واهليلج الانيزوتروبية لتوضيح البنية الجيولوجية واقتراح الموقع المناسب لإنشاء سد باشكات. The Bashkat dam is situated on the western ridg of Al-Anssary Mountain, region of Lattakia conservation where the dam has been chosen to be constructed. The aim of this study is to overcome some geo-engineering questions such as: - Study of Weathering Layer. - clarify theGeological structure of Bashkat dam site. - demonstrate the caves and spaces karists. - determine the fault zones in the site. - determine zones Fractures and its general direction. - determine the specific water Factor absorption for geoelectrical beds. - determine the clay content for geoelectrical beds (β %). - drawing up a geological map to study area, scale(1:2000). To resolve the above mentioned questions,we have used the resistivity method using Schlumbergger configuration for vertical electric sounding(VES) and circular electric sounding. This work covered (34) soundig points dipersed in five profiles. After interpretation of vertical and circular sounding by manual methods,we have reached that five geoelectrical sections and anisotropic spheroid were made to clarify the geological structure and to suggest the convenient site for dam construction.